Endothelial progenitor cells modulate the phenotype of smooth muscle cells and increase their neointimal accumulation following vascular injury. (14th October 2021) - Mause, S; Ritzel, E; Deck, A; Vogt, F; Liehn, E
Abstract: Background: Smooth muscle cells (SMCs) are the main driver of neointima formation and restenosis following vascular injury. In animal models, endothelial progenitor cells (EPCs) accelerate endothelial regeneration and reduce neointima formation after arterial injury, however EPC-capture stents do not to reduce target vessel failure compared to conventional stents. Here we examined the influence of EPCs on features of SMCs pivotal for their impact on neointima formation including proliferation, migration and phenotype switch. Methods and results: EPCs, their conditioned medium and EPC-derived microparticles induced proliferation of SMCs while limiting their apoptosis. In transwell membrane experiments and scratch assays EPCs stimulated migration of SMCs and accelerated their recovery from scratch-induced injury. Treatment of SMCs with EPC-derived conditioned medium or microparticles triggered transformation of SMCs towards a synthetic phenotype. However, co-cultivation of EPCs and SMCs enabling direct cell-cell contacts preserved their original phenotype and protected from the transformative effect of SMC cholesterol-loading. Adhesion of EPCs to SMCs was stimulated by SMC injury and reduced by blocking CXCR2 and CCR5. Interaction of EPCs with SMCs modulated their secretome and synergistically increased the release of selected chemokines. Following carotid wire injury in athymic mice, injection of EPCs resulted not only in reduced neointima formation but also in altered cellular composition of the neointima with augmented accumulation of SMCs. Conclusion: EPCs stimulate proliferation and migration of SMCs and increase their neointimal accumulation following vascular injury. Furthermore, EPCs modify the SMC phenotype with protection from the transformative effect of cholesterol when direct cell-cell contact is established. FUNDunding Acknowledgement: Type of funding sources: None.